PENGARUH RISIKO KREDIT, LIKUIDITAS DAN PERMODALAN TERHADAP KINERJA PERBANKAN DI BURSA EFEK INDONESIA - Jayanti, Putu Kristy; Panji Sedana, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.08.TAHUN.2023DO - 10.24843/EEB.2023.v12.i08.p17, 2023)
The banking industry play an important role in the development of the Indonesian economy, because act as intermediary institutions between parties who have excess funds and those who need funds. In bank operations, credit risk, liquidity management, and capital can be said to have high risk potential. The purpose of this study was to examine the effect of credit risk, liquidity, and capital on banking performance. Bank performance can be used as a basis for measuring whether the bank has carried out management activities in accordance with sound banking regulations in accordance with applicable regulations. The population in this study were 43 conventional commercial banks listed on the Indonesia Stock Exchange for the period 2018 to 2020. The sampling technique in this study was the purposive sampling method, namely the sampling method based on certain criteria and considerations. The sample in this study were 38 banking companies. The analytical technique used in this research is multiple linear regression analysis. The results of this study indicate that credit risk has a negative effect on banking performance, while liquidity has a positive effect on banking performance and capital has a positive effect on banking performance